Sonographic Findings of Accessory Breast Tissue in Axilla and Related Diseases. (3rd April 2017) - Lim, Hyo Soon; Kim, Shin Jung; Baek, Jang Mi; Kim, Jin Woong; Shin, Sang Soo; Seon, Hyun Ju; Heo, Suk Hee
Abstract : Accessory breast tissue results from failed regression of primitive mammary tissue and is most often located in the axilla. Accessory breast tissue itself is normal and should not be misdiagnosed as an abnormality. Both benign and malignant diseases that occur in the normal breast can also develop in accessory breast tissue in the axilla. In this pictorial essay, we show sonographic findings of normal accessory breast tissue in the axilla and various lesions that occur in accessory axillary breast tissue, along with other imaging findings and pathologic features.